Action research in the light of integrative practice of marital and family therapists and some other research problems - Cvetek, Robert; Cvetek, Mateja; Gostecnik, Christian (European Journal for Qualitative Research in Psychotherapy, 2008)
Marital and family therapists are likely to use multiple models or treatment approaches, combine several techniques, theories, or factors in their therapy to address the complexity of the therapeutic situation and abandon or modify “pure” theories and models. That makes research in marital and family therapy (MFT) even more complicated, especially when we talk about the applicability for practitioners. The practice of the majority of MFT practitioners is very individualized or idiographic, as are the clinical problems and circumstances. Action research method, which has been mainly overlooked in MFT research, is suggested to be able to help with some of the problems in MFT, although it has its own limitations and weaknesses. One of the possible ways of using repeating cycles of the four basic steps in action research (gathering information, reflecting, planning and acting) is described and briefly discussed.